Peran Pos Kesehatan Pesantren pada Pencegahan Kejadian Scabies di Pondok Pesantren (Studi Kualitatif) - Nurlita, Diah; Rahman, Asep Abdul (Jurnal Kesehatan, 2022)
Scabies is one of the infectious diseases that have not lost its prevalence in Indonesia. The prevalence of scabies in Indonesia in 2008 was 5.6% -12.95%. Scabies ranks third of the 12 most common skin diseases. Scabies is a common disease in boarding schools which is the result of dense occupancy, poor sanitation, and poor personal hygiene of students. Preventive Efforts are perceived as the most effective effort to Prevent scabies disease since disease Scabies treatment still leaves side effects and drug resistance. The purpose of this research is to know the description of the role of Poskestren in the prevention of disease scabies in Tasikmalaya City. The design of this research is descriptive and qualitative. The population of this research is the whole boarding school in Tasikmalaya City Health Post that has Pesantren. This research was conducted at Ruwada Medika Clinic roommates owned by Pesantren Riyadlul 'Ulum Wadda'wah Lean Cibeureum district. Promotion Efforts conducted by Poskestren for the prevention of scabies disease are in the form of counseling about PHBs at a predetermined time, providing additional nutrients and vitamins to maintain health Santri. As for preventive Efforts for the prevention of Scabies is to move the organization in the boarding school students to invite and implement the rules in the cottage, especially in terms of the maintenance of the cleanliness student room.